1968
DOI: 10.1113/jphysiol.1968.sp008500
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prostaglandins E1, F and F on monosynaptic reflexes

Abstract: SUMMARY1. Experiments, using electrophysiological recording techniques, were carried out to confirm the report that prostaglandins affect spinal reflexes in cats.2. Ventral root potentials evoked by stimulation of the ipsilateral dorsal root were recorded. Those with a latent period corresponding to a monosynaptic pathway were used primarily in this investigation. 6. It is concluded that prostaglandins, two of which have previously been identified in cat brain extracts, have pronounced and long-lasting effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1968
1968
1990
1990

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Cardiovascular effects elicited by intracarotid infusion of PGE1 in intact dogs, or in cross-circulation experiments, are abolished by ganglion blocking drugs (127,128). At least part of these effects are presumably mediated by the central nervous system, where PGs are capable of either stimulating or inhibiting ganglionic trans mission (129)(130)(131) The adrenal medullary cells are homologues to postganglionic nerve cells, and the nerve-effector cell junction may therefore be regarded as a specialized type of ganglionic transmission. It has been shown that PGE1 and PGF1a do not modify resting outflow or increased secretion of catecholamines induced by acetylcholine, potassium, or splanchnic nerve stimulation in the cat (132).…”
Section: Ganglionic Transmissionmentioning
confidence: 96%
“…Cardiovascular effects elicited by intracarotid infusion of PGE1 in intact dogs, or in cross-circulation experiments, are abolished by ganglion blocking drugs (127,128). At least part of these effects are presumably mediated by the central nervous system, where PGs are capable of either stimulating or inhibiting ganglionic trans mission (129)(130)(131) The adrenal medullary cells are homologues to postganglionic nerve cells, and the nerve-effector cell junction may therefore be regarded as a specialized type of ganglionic transmission. It has been shown that PGE1 and PGF1a do not modify resting outflow or increased secretion of catecholamines induced by acetylcholine, potassium, or splanchnic nerve stimulation in the cat (132).…”
Section: Ganglionic Transmissionmentioning
confidence: 96%
“…Pharmacological actions of prostaglandin E1 (PGE1) on the central nervous system (CNS) have been demonstrated in cats by injection into the cerebral ventricles (Horton, 1964;Horton & Main, 1965), by micro-iontophoretic application (Avanzino, Bradley & Wolstencroft, 1966), by intravenous injection (Horton & Main, 1967) and by close-arterial injection to the spinal cord (Duda, Horton & McPherson, 1968). Although only relatively small doses are required to produce these effects in cats and also on intravenous injection in young chicks (Horton, 1964;Horton & Main, 1965, 1967, it has been shown in other species (rats, mice and sheep) that little or no tritium-labelled prostaglandin E1 reaches the CNS following intravenous injection (Hansson & Samuelsson, 1965;Samuelsson, 1964Samuelsson, , 1965.…”
mentioning
confidence: 99%
“…Furthermore, the excitatory and inhibitory effects of PGE1, PGE2 or PGF2a on brain stem neurones was followed by a unique desensitization, specific for the compound applied (Avanzino et al, 1966). The PGF compounds have a strychnine-like action on the spinal cord of the chick (Horton & Main, 1967b) and on intra-arterial injection close to the spinal cord they produce a reduction in the monosynaptic reflex which is slow in onset and lasts for up to 3 hr (Duda, Horton & McPherson, 1968). These findings, together with the fact that prostaglandins can protect mice against death from electroshock (Holmes & Horton, 1968b), may also be explained in terms of a long-lasting depolarization, which would suggest that the prostaglandins modify neuronal activity by an action on the cell memfbrane.…”
Section: Discussionmentioning
confidence: 99%